Body image dissatisfaction and disordered eating behaviors in Chinese female undergraduate students: the mediating role of emotional regulation strategies - Danli He; Harvinder Kaur Gilcharan Singh; Masoumeh Alavi; Hui Chin Koo; Muhamad Nur Fariduddin; Lei Hum Wee; Ching Sin Siau (Journal of Eating Disorders)
Abstract Background Female undergraduates are a high-risk population for body image dissatisfaction and eating disorder symptomatology. This study aimed to investigate the prevalence of body image dissatisfaction and disordered eating behaviors, as well as to examine the mediating roles of two emotion regulation strategies (cognitive reappraisal and expressive suppression) on the relationship between body image dissatisfaction and disordered eating behaviors among female undergraduate students in China. Methods A total of 1756 Chinese female students, with a mean age of 19.8 years (SD = 1.5), were included in the study. Participants completed an online survey comprising items related to body image dissatisfaction, emotion regulation, and disordered eating behaviors. Covariance-based structural equation modeling (CB-SEM) technique was employed, with the hypothesized parallel mediation model tested using 10,000 bootstrap samples. Results More than half of the participants (60.5%, n = 1063) reported body image dissatisfaction and demonstrated high levels of disordered eating behaviors, including uncontrolled eating (52.5%, n = 922), emotional eating (54.0%, n = 948), and cognitive restraint (57.4%, n = 1008). Cognitive reappraisal partially mediated the associations between body image dissatisfaction and uncontrolled eating (b = 0.047, 95% CI [0.035, 0.061]), emotional eating (b = 0.047, 95% CI [0.035, 0.062]), and cognitive restraint (b = 0.040, 95% CI [0.029, 0.055]). Expressive suppression also showed partial mediating effects in these associations: uncontrolled eating (b = 0.055, 95% CI [0.042, 0.072]), emotional eating (b = 0.053, 95% CI [0.040, 0.070]), and cognitive restraint (b = 0.053, 95% CI [0.038, 0.069]). Further, there were direct effects of body image dissatisfaction on uncontrolled eating (b = 0.165, 95% CI [0.125, 0.205]), emotional eating (b = 0.183, 95% CI [0.140, 0.226]), and cognitive restraint (b = 0.196, 95% CI [0.153, 0.240]). Conclusions This study found that both cognitive reappraisal and expressive suppression partially mediated the relationship between body image dissatisfaction and disordered eating behaviors, underscoring the importance of targeting emotion regulation strategies in prevention and early intervention efforts among Chinese female undergraduates.